مقياس المخالفة للوقائع والأحداث التاريخية وأثره في نقد متن الحديث - عبد اللاوي, يوسف (جامعة الوادي University of Eloued, 2016)
مقياس عرض السنة على الوقائع والأحداث التاريخية لاكتشاف خلل في متونها أو فساد في معانيها، من المقاييس التي لها وزنها في الساحة النقدية، وقد استعان بها عدد من علماء الحديث وحاكموا بعض الأحاديث إليها، فمنها ما حُكِم عليه بالوضع بعد اكتشاف مخالفة الحديث للواقع التاريخي الثابت وهو الغالب، ومنها ما حُكم له بخطإ الراوي ونكارة الحديث وغرابته بذلك اللفظ، مع التماس المحامل والمخارج للحديث وراويه كما هو واضح في الأمثلة التي سنوردها في بحثنا. مع التنبيه على أن الحدث التاريخي يسقط الاعتبار به إذا كان مشكوكا في ثبوته، أو له أكثر من وجه في المعنى. Abstract: Facts and historical events is one of the measures by which we judge the Hadith and to recognize the imbalance in the text ( metn) or weakness in the meanings. This measure has a notable value in the view of scientists , and by which we judge some of the ahaadeeth that are Unacceptable because of the weakness of his narrator. Some other are judged by lying. With the observation that scientists are always looking for a possible remedies. It is what we will see in the illustrative examples Noting that Facts and historical events are not acceptable in case of doubt.
Measure Contravention Of The Facts And Historical Events And Their Impact On The Text (metn El-hadith)
Keywords: الحديث النبوي، التاريخ، النقد، الوقائع، النص; Prophetic Hadith, history, criticism, facts, the text